2014
DOI: 10.1177/1049909114559068
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Educational Needs of Neonatologists and Neonatal Nurses Regarding Palliative Care in Taiwan

Abstract: Survey data from neonatologists and neonatal nurses in Taiwan indicate a need for further training on a range of neonatal palliative care competencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
(45 reference statements)
2
17
0
4
Order By: Relevance
“…Most nurses had a good level of knowledge of pain management, but a few reported negative attitudes towards the use of pharmacological agents during painful procedures such blood sampling or EET for critically ill neonates admitted to intensive care units. Negative attitude have been reported in other studies as the main barriers in pain assessment and alleviation [18,19].…”
Section: Discussionmentioning
confidence: 81%
“…Most nurses had a good level of knowledge of pain management, but a few reported negative attitudes towards the use of pharmacological agents during painful procedures such blood sampling or EET for critically ill neonates admitted to intensive care units. Negative attitude have been reported in other studies as the main barriers in pain assessment and alleviation [18,19].…”
Section: Discussionmentioning
confidence: 81%
“…The association between clinicians’ previous PC education and their knowledge has been described widely in different health-care students and professionals both at undergraduate and postgraduate levels. 32 -35 In addition, a greater level of education in PC was associated with higher levels of comfort to work with PPC patients. 36 Similarly, our study found that PC education was not only the factor that increased PC knowledge the most but also increased by 4.3 times the probability of feeling comfortable discussing PC needs.…”
Section: Discussionmentioning
confidence: 99%
“…We designed multiple training models on pediatric palliative care, based on the Framework of Competencies for Level 3 Pediatric Palliative Care Education (Gamondi et al, 2013) and the known educational needs of pediatric clinicians (Kolarik et al, 2006; Lee et al, 2016; Michelson, Ryan, Jovanovic, & Frader, 2009; Peng et al, 2013). The material was presented as a 4-day training conference in Taichung City, Taiwan, and comprised the main curriculum and the supplemental courses.…”
Section: Methodsmentioning
confidence: 99%
“…The main curriculum was the internationally recognized End-of-Life Nursing Education Consortium-Pediatric Palliative Care (ELNEC-PPC) course, which covers 10 topics and provides the learners with PowerPoint slides and additional resources to enhance the learning experience (Jacobs, Ferrell, Summer, & Malloy, 2010; Malloy, Ferrell, Virani, Wilson, & Uman, 2006). The supplemental training courses addressed ethical and communication issues tailored to the specific educational needs of clinicians in Taiwan (Huang et al, 2013; Lee et al, 2016; Peng et al, 2013). A variety of educational strategies were used, including didactic lectures, case study discussions, role-play, and video viewings; two sessions of panel discussion were also included in the supplemental training.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation